2018
DOI: 10.1016/j.schres.2018.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Targeted cognitive training improves auditory and verbal outcomes among treatment refractory schizophrenia patients mandated to residential care

Abstract: Computerized targeted cognitive training (TCT) of auditory processing has been shown to improve verbal learning in several clinical trials of schizophrenia outpatients. Less is known, however, about the effectiveness of this promising intervention in more chronic, treatment-refractory patients who are treated in non-academic settings. This study aimed to determine whether TCT improves auditory processing, verbal learning, and clinical symptoms in SZ patients mandated to receive care at a locked residential reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 53 publications
2
53
1
Order By: Relevance
“…[37]), and determine whether this malleability predicts TCT outcomes after a 30 h course of treatment. We have previously reported a favorable TCT response in this cohort [15], with significant improvements in MCCB verbal learning t-scores (d = 0.65-082), and reductions in auditory hallucinations (d = −0.58), consistent with existing literature [6]. Based on our previous report [37], we hypothesized that there would be significant changes in MMN and P3a in recordings completed immediately before and after the 1st hour of TCT, and that the degree of this initial change would predict post-treatment improvements in verbal learning and positive symptom severity.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…[37]), and determine whether this malleability predicts TCT outcomes after a 30 h course of treatment. We have previously reported a favorable TCT response in this cohort [15], with significant improvements in MCCB verbal learning t-scores (d = 0.65-082), and reductions in auditory hallucinations (d = −0.58), consistent with existing literature [6]. Based on our previous report [37], we hypothesized that there would be significant changes in MMN and P3a in recordings completed immediately before and after the 1st hour of TCT, and that the degree of this initial change would predict post-treatment improvements in verbal learning and positive symptom severity.…”
Section: Introductionsupporting
confidence: 54%
“…The "bottom up" approach of TCT is congruent with mounting evidence that abnormalities in early auditory information processing (EAIP) substantially contribute to impairments in higher-order cognitive and psychosocial functioning [10][11][12][13][14][15][16]. Efficacy trials in schizophrenia patients have shown that TCT improves higher-order cognitive functioning [6,9,15,[17][18][19][20], particularly in the domain of verbal learning. However, individual responses to TCT vary, with up to 45% of patients exhibiting minimal or no benefit even after extended therapeutic "doses" [21].…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…These will improve our understanding of adult plasticity and help devise better rehabilitation strategies for patients with perceptual and cognitive impairments (Kantrowitz et al, 2018;Thomas et al, 2018).…”
Section: Discussionmentioning
confidence: 99%